2000
DOI: 10.1080/095006900416848
|View full text |Cite
|
Sign up to set email alerts
|

Interactive multimedia and model-based learning in biology

Abstract: This paper documents a case of model-building in biology through microanalysis of one student's interaction with 'Science for Living: The Circulatory System' (SFL), an interactive multimedia resource prototype for research. When SFL was used in a technology-rich, tenth grade (15-16 years of age) biology classroom, extensive data ranging from preconceptions tests to videotapes, projects and computer logs of work sessions were collected. This paper describes the student's learning goals, gains and activities wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 47 publications
2
94
0
12
Order By: Relevance
“…Students may find it difficult to understand the concept of blood circulation because it is invisible and hard to experience. It also involves a wide range of concepts, such as blood cells, oxygen, carbon dioxide, heart valves, heart, blood vessels, blood pressure, and so on (Buckley 2000). Each lesson consisted of 45 min in which the teacher guided the process of hands-on activities around the target phenomena for group modeling, and students practiced the hands-on activities and participated in small-groups and class discussions.…”
Section: Task Characteristics Of the Implemented Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students may find it difficult to understand the concept of blood circulation because it is invisible and hard to experience. It also involves a wide range of concepts, such as blood cells, oxygen, carbon dioxide, heart valves, heart, blood vessels, blood pressure, and so on (Buckley 2000). Each lesson consisted of 45 min in which the teacher guided the process of hands-on activities around the target phenomena for group modeling, and students practiced the hands-on activities and participated in small-groups and class discussions.…”
Section: Task Characteristics Of the Implemented Lessonsmentioning
confidence: 99%
“…Since the concept of blood circulation is difficult for students to experience or observe directly, it is easy for students to misunderstand it (Buckley 2000;Chi 2005). Students need to have comprehensive thinking skills in order to understand the interaction between the functions of the elements in the circulatory system, and their structures at the cellular, organ, and organ system levels.…”
Section: Introductionmentioning
confidence: 99%
“…External models shape or give rise to students' mental models and students' preexisting mental models inßuence their perception of phenomena and understanding of external models (Buckley, 2000;Buckley & Boulter, 2000;Rohr & Reimann, 1998). For example, a case study by Rohr and Reimann (1998) revealed that students' beliefs, perceptions of phenomena, and explanations of external representations interact and coevolve over the course of learning with multiple representations.…”
Section: Using Models To Support Students In Learning Chemistrymentioning
confidence: 99%
“…They provide a means for making visible phenomena that are too small, large, fast, or slow to see with the unaided eye. Similarly, visual representations illustrate invisible or abstract phenomena that cannot be observed or experienced directly (Buckley, 2000). In science, graphics are also used to display data, organize complex information, and promote a shared understanding of scientific phenomena (Kozma, 2003).…”
Section: Introductionmentioning
confidence: 99%